CARIES STATUS OF STUDENTS OF THE FACULTY OF ODONTO-STOMATOLOGY, HANOI UNIVERSITY OF BUSINESS AND TECHNOLOGY IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of dental caries among students of the Faculty of Odonto-Stomatology, Hanoi University of Business and Technology in 2024.Subjects and methods: A cross-sectional descriptive study was conducted to determine the prevalence of dental caries among 101 students of the Faculty of Odonto-Stomatology, Hanoi University of Business and Technology, from January to June 2024.Results: The prevalence of dental caries among these students, as diagnosed by ICDAS II was 77.23%, with early-stage caries accounting for 54.05%. The DMFT index was 4.7 ± 3.23 (D: 1.6; M: 0.52; F: 2.58). The prevalence of dental caries and the DMFT index were classified as high according to WHO standards. Dental caries mainly occurs on the occlusal surface, accounting for 40.11% of cases.Conclusion: The DMFT index of students of the Faculty of Odonto-Stomatology, Hanoi University of Business and Technology is high, with a higher rate of cavities in males than in females, and higher in area I than in areas II and III.
Keywords: Dental caries, DMFT, early-stage caries, odonto-stomatology students.